Cognitive Restructuring and Graded Behavioural Exposure for Delusional Appraisals of Auditory Hallucinations and Comorbid Anxiety in Paranoid Schizophrenia. (11th September 2014) - Mankiewicz, Pawel D.; Turner, Colin
Abstract : The prevalence of diagnostic comorbidity between psychosis and anxiety disorders has been found to be considerable. Cognitive models of psychosis suggest that anxiety does not arise directly from positive symptoms of schizophrenia but rather from an individual interpretation of such experiences. In the United Kingdom, cognitive-behavioural therapy for psychosis (CBTp) has been recommended within clinical guidelines as a psychological treatment of choice for those diagnosed with schizophrenia. However, despite empirical evidence supporting CBTp, the treatment provision remains infrequent and not routinely available. This case describes a successful implementation of CBTp. Sixteen sessions were delivered to a 40-year-old male with diagnoses of paranoid schizophrenia and comorbid anxiety, focusing primarily on cognitive restructuring of paranoid appraisals of auditory hallucinations and behavioural experiments employed progressively via graded exposure to anxiety-inducing stimuli. Standardised measurements, behavioural frequency sampling, and subjective data indicated a considerable reduction in both paranoia and anxiety. Also, the client's psychosocial functioning improved substantially. This report indicates that the treatment may help those with experiences of psychosis and comorbid anxiety reach a significant improvement in their quality of life and offers an encouraging and innovative perspective on direct engagement with the content of paranoia and voices at the onset of therapy.